2010
DOI: 10.1063/1.3483690
|View full text |Cite
|
Sign up to set email alerts
|

Communication: An extended model of liquid bridging

Abstract: Recent phenomenological studies have drawn attention to an appealing effect, observed for the first time in 1893, today known as water-bridge. The phenomenon has been ascribed to unknown properties of water. We report some experimental results showing that, contrary to a widely common belief, the phenomenon is not to be related with water neither with a property of hydrogen bonded networks. Using a very simple model, we show that the liquid bridge phenomenon is originated by electrostatic effects and can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…It has been even supposed that WB stability against gravity is a quantum effect [10].However, the best explanation of a newly discovered phenomenon is the simplest one based on well known formulas. It has been stated already [7,11] that not specific properties of water but just its high dielectric permittivity is likely to be the reason of the WB phenomenon. The convincing evidence of the statement is the "water bridge" (dielectric liquid bridge (DB)) formation of another low molecular polar dielectric liquid (DL): glycerine [9].…”
mentioning
confidence: 99%
“…It has been even supposed that WB stability against gravity is a quantum effect [10].However, the best explanation of a newly discovered phenomenon is the simplest one based on well known formulas. It has been stated already [7,11] that not specific properties of water but just its high dielectric permittivity is likely to be the reason of the WB phenomenon. The convincing evidence of the statement is the "water bridge" (dielectric liquid bridge (DB)) formation of another low molecular polar dielectric liquid (DL): glycerine [9].…”
mentioning
confidence: 99%
“…This phenomenon, first ascribed to some unknown properties of water, finally revealed to be originated just by dielectric forces. 20,21 In particular, the phenomenon is observed also in pure dielectric liquids where the deformation of the free liquid surface under an intense electric field is originated by the interaction of the electric field with the existing (both permanent and induced) dipoles while no free charge carriers can be hypothesized.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…6 To build up such a liquid bridge under an applied electric field, some researchers believe that the liquid must have a high dielectric permittivity, a low electric conductivity, and a permanent molecular dipole moment. 4,7-10 However, Saijia et al 11 suggested that the liquid bridges can be produced in any dense fluid. No matter whatever the origin may be, the floating water bridges are essentially related to electricity.…”
Section: Introductionmentioning
confidence: 97%
“…The study of this phenomenon was revived by Fuchs et al 2 in 2007. Thereafter, a number of research works [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have been devoted to the floating water bridges between the deionized water in two containers induced by the high voltages applied to the deionized water. However, the interpretations to the origin of the floating water bridges are different at present stage, 3 for example, dielectric tension, 4 surface tension, 5 or both.…”
Section: Introductionmentioning
confidence: 99%